Challenges of Converting an In-person Dance Course to a MOOC Course - Chantre Astaiza, Angela Rocio; Burbano Astaiza, Claudia Patricia; Solarte Sarasty, Mario Fernando (Revista Ingenierías Universidad de Medellín, 2021)
This article presents the design experience of the ’Folk dance as cultural heritage’ course, which is offered to undergraduate students from University of Cauca the ’massive online course’ modality. It shows the main challenges faced in the exercise of the integration of two in-person courses, one practical and one theoretical, and its process of transformation into a MOOC. The course was designed for two academic credits with six hours of dedication per week and is offered as an elective (non-mandatory) class of the Integral Social and Human Formation (FISH) component, through a space in the MOOC Open edX platform. The integration process of the two in-person courses and their transformation into a MOOC, brought with it several challenges related to the adjustment of contents, academic activities and evaluation. This article presents how these challenges were faced in this experience. It is worth mentioning that one of the results obtained in this research is associated with the contribution of the research to the first folk dance course in MOOC modality in Latin America, what makes it an innovative educational proposal that allows the rescue of culture through the adaptation of traditional educational contents.